“A Cartomante”, um conto de Machado de Assis para incentivar a competência leitora e a escrita de alunos do ensino fundamental - CORREA, Ana Carolina Pinheiro (2024)
This paper reports on the experiences of Supervised Internship II: Portuguese Language and its Literatures in Elementary School (6th to 9th grade). Following this, it aims to observe and reflect on issues related to reading and writing of elementary school students, based on the experiences obtained during the internship. The methodology was developed from investigative research in the school context, therefore, the research field was a public school in the city of Bragança-PA, in a 9th grade E.F. class. For this, a lesson plan was developed to be implemented, based on studies and theoretical references by authors such as: Pimenta (2004, p.99), Normanda Bezerra (2004), Beth Marcuschi (2000), among others who discuss the theme. With this, it is expected that the perspective addressed by this study will contribute to a better understanding of issues related to the educational space in the context of working with literature.